Photo-thermal super-hydrophobic anti-icing and deicing composite material based on template collaborative ablation method, preparation method of photo-thermal super-hydrophobic anti-icing and deicing composite material and photo-thermal super-hydrophobic anti-icing and deicing surface
The superhydrophobic surface is prepared by template collaborative ablation method, combined with flame ablation and the use of photothermal nanoparticles, and the problems of complex and high cost in the existing technology are solved, and efficient and low-cost superhydrophobic surface preparation is achieved. , has excellent passive anti-ice and photothermal active deicing properties.
Patent Information
- Application Number
- CN202411563875.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The prior art has problems such as complex preparation process, high etching cost and long processing time when preparing superhydrophobic surfaces, making it difficult to achieve large-scale production, and there is a lack of simple and effective methods to build superhydrophobic surfaces to achieve passive anti-ice effect. .
Using the template collaborative ablation method, sandpaper is used as the template to form a film with a micro-pit structure by casting and curing, and then using flame ablation treatment, nano-folds or synapses are formed on the micro-pit structure of the film. Nanoparticles, thereby forming a superhydrophobic surface with micro-nano structure, and photothermal nanoparticles are added to the surface to achieve the photothermal active deicing function.
It realizes a superhydrophobic surface with a simple process, short preparation time and low cost, which is suitable for large-scale production and improves the ability to resist ice by passively. It also has the function of active deicing of light and thermal energy, and optimizes the anti-icing and deicing strategies.
Smart Images

Figure CN119410007A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of multifunctional super-hydrophobic materials, and in particular to a photothermal super-hydrophobic anti-icing and deicing composite material based on a template collaborative ablation method, a preparation method thereof, and a photothermal super-hydrophobic anti-icing and deicing surface. Background Art
[0002] At present, in order to eliminate ice and frost accumulation on the surface of equipment or equipment, there are active deicing technology and passive deicing technology. Among them, active deicing technology includes mechanical deicing, chemical deicing and electrothermal deicing methods. However, these active deicing technologies have the disadvantages of low deicing efficiency, high energy consumption, high maintenance cost, environmental pollution and operational risks in practical applications. In recent years, passive anti-icing technology has received widespread attention from researchers and industry. Researchers have successively developed and reported a variety of passive anti-icing surfaces, such as super-hydrophobic surfaces, anti-freeze surfaces and sliding surfaces. Compared with sliding surfaces and anti-freeze surfaces, super-hydrophobic surfaces have the advantages of outstanding anti-icing effect and easier large-scale production.
[0003] In the prior art, the main idea of preparing super-hydrophobic surface is to realize by combining surface micro-nano composite structure with low surface energy material. Among them, the Chinese patent application with publication number CN110746624A discloses a PDMS super-hydrophobic surface preparation method based on template method. The patent application first performs laser processing on the metal substrate to obtain a microstructure array, and then performs the method of PDMS reverse molding to obtain a super-hydrophobic surface. In addition, the Chinese patent application with publication number CN106185792A discloses a fully parameter controllable preparation method of a super-hydrophobic micro-nano composite structure. The patent application proposes a method combining micro-electromechanical lithography technology and colloidal soft etching, assembling nano-microspheres into a single-layer dense nano mask by self-assembly, and then combining with a silicon substrate with a micron structure, preparing a micro-nano composite structure by oxygen plasma etching and colloidal soft etching, and finally modifying with fluorosilane to obtain a super-hydrophobic surface. However, the above-mentioned technologies for preparing super-hydrophobic surfaces all need to obtain micro-nano structures as templates through complex mechanical / laser processing, and then perform replication of micro-nano structures to obtain super-hydrophobic surfaces. Other template methods in the prior art include replicating super-hydrophobic organisms, electrochemical deposition and porous membranes. With the development of laser processing, laser ablation to engrave super-hydrophobic patterns is also an effective method. However, the limitation of the template is not conducive to large-area preparation, and the preparation and processing of the template may increase the cost. In addition, with regard to laser ablation, although the emergence of femtosecond and picosecond lasers has greatly shortened the processing time, large-scale processing equipment is required, and the equipment cost is particularly high.
[0004] It can be seen that the existing technology for preparing super-hydrophobic surface has problems such as complex preparation process, high etching cost and long processing time, which makes it difficult to achieve large-scale production in industry. Therefore, in the development of super-hydrophobic anti-icing and de-icing surfaces, a simpler and more effective method is used to construct super-hydrophobic surfaces to achieve the effect of passive anti-icing, and the technology in this area is not mature enough. In addition, the passive anti-icing technology of super-hydrophobic surfaces is combined with the active photothermal deicing technology. This anti-icing and de-icing strategy has significant advancement and feasibility, and is practical for solving the ice accumulation and frost on the surface of current outdoor equipment or equipment. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the first purpose of the present invention is to provide a method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on a template-coordinated ablation method. The preparation method uses sandpaper as a template, and forms a thin film with a micro-pit structure by a casting and curing film-forming method. Then, through flame ablation treatment, nano-wrinkles or synapse-like nanoparticles are formed on the micro-pit structure of the film, thereby forming a super-hydrophobic surface with a micro-nano structure. Compared with other current technologies, the method has the advantages of simple process, short preparation time, and suitability for large-scale production.
[0006] In order to overcome the shortcomings of the prior art, the second purpose of the present invention is to provide a photothermal super-hydrophobic anti-icing and deicing composite material based on template collaborative ablation method, which utilizes the micro-pit structure of the sandpaper template combined with the nano-folds or nano-synapses obtained by ablation to realize the super-hydrophobic Cassie-Baxter model of the surface, increase the water contact angle, reduce the rolling angle, and reduce the adhesion of ice and other contaminants, thereby enhancing the passive anti-icing ability; by adding nanoparticles with photothermal properties, the composite material also has the function of photothermal active deicing.
[0007] The third object of the present invention is to provide a photothermal super-hydrophobic anti-icing and deicing surface, which has excellent hydrophobicity, anti-icing and deicing properties, and has low preparation cost, high preparation efficiency, and can be mass-produced in industry.
[0008] In order to achieve the first object of the above invention, the technical solution adopted by the present invention is as follows:
[0009] The present invention provides a method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on a template coordinated ablation method, comprising the following steps:
[0010] S1. preparing film-forming slurry: adding high molecular polymer and photothermal nanoparticles into an organic solvent, mixing them evenly, and preparing film-forming slurry;
[0011] S2, reverse molding: using sandpaper as a template, pouring the film-forming slurry prepared in step S1 on the surface of the sandpaper;
[0012] S3, curing and demoulding: heating and curing the film-forming slurry poured on the sandpaper surface in step S2, and then removing the sandpaper template to obtain a film with a micro-pit structure on the surface;
[0013] S4, flame ablation treatment: using flame to ablate the surface of the film obtained in step S3, so as to obtain the photothermal super-hydrophobic anti-icing and deicing composite material based on template coordinated ablation method.
[0014] The present invention discloses a photothermal super-hydrophobic anti-icing and deicing composite material based on a template coordinated ablation method and a preparation method thereof. Photothermal nanoparticles are used as fillers and uniformly dispersed in a high molecular polymer. Sandpaper is then used as a template to form a film with a micro-pit structure by a casting and curing film-forming method. Then, nano-wrinkles or synapse-like nanoparticles are formed on the micro-pit structure of the film by flame ablation treatment, thereby forming a super-hydrophobic surface with a micro-nano structure. The prepared photothermal super-hydrophobic anti-icing and deicing composite material based on a template coordinated ablation method has excellent photothermal and hydrophobic properties and can be used as a photothermal super-hydrophobic anti-icing and deicing surface. The present invention is simple in the entire preparation process of the super-hydrophobic anti-icing and deicing material, from the selection of the template to the formation of the micro-nano structure of the photothermal super-hydrophobic surface, with low preparation cost, short preparation time, and high preparation efficiency, and can be suitable for large-scale production.
[0015] Furthermore, in step S1, the high molecular polymer is polydimethylsiloxane, which is a high molecular polymer with low surface energy and its film-forming material has good hydrophobic properties. And / or
[0016] The photothermal nanoparticles are one of carbon black nanoparticles, ferroferric oxide nanoparticles or titanium dioxide nanoparticles; wherein the photothermal nanoparticles have excellent photothermal conversion performance. And / or
[0017] The organic solvent is one of n-hexane, ethyl acetate or tetrahydrofuran, wherein n-hexane, ethyl acetate or tetrahydrofuran are all easy to dissolve polymer compounds and are easy to volatilize during heating and curing.
[0018] Furthermore, in step S1, the mass ratio of the high molecular weight polymer, the organic solvent and the photothermal nanoparticles is 1:(1.5-3):(0.002-0.01); and / or
[0019] The particle size of the photothermal nanoparticles is 20nm to 40nm; wherein the particle size of the photothermal nanoparticles can make the formed material have better hydrophobic properties. And / or
[0020] The uniform mixing is carried out by using a high-speed homogenizing and degassing machine. The speed of the high-speed homogenizing machine is 3000 rap to 4000 rap, and the homogenizing time is 3 min to 5 min. The degassing allows the film-forming slurry to better fit the sandpaper template, and the cured film can replicate the morphology of the sandpaper template, which can make the film more hydrophobic.
[0021] Furthermore, in step S1, the film-forming slurry after being mixed evenly is further placed in a vacuum tank for vacuum degassing. Through further vacuum degassing, the film-forming slurry and the sandpaper template are better fitted, and the cured film can more highly and completely replicate the morphology of the sandpaper template, so that the obtained film can have excellent hydrophobic properties.
[0022] Furthermore, in step S2, the mesh number of the sandpaper is 100 to 800. Preferably, the mesh number of the sandpaper is 240 to 400.
[0023] Furthermore, in step S2, the sandpaper is fixed in a container, and the film-forming slurry obtained in step S1 is poured on the surface of the sandpaper. The sandpaper is fixed in a container to facilitate the subsequent heating, curing and molding process.
[0024] Furthermore, in step S3, the temperature of the heating and curing is 60° C. to 80° C., and the time of the heating and curing is 2 h to 4 h. The heating and curing is performed in an oven.
[0025] Furthermore, in step S4, the flame is a flame of butane combustion; and / or
[0026] The temperature of the flame is 500° C. to 700° C., and the time of the ablation treatment is 5s to 25s.
[0027] In order to achieve the second purpose of the above invention, the technical solution adopted by the present invention is as follows:
[0028] The present invention provides a photothermal super-hydrophobic anti-icing and deicing composite material based on a template collaborative ablation method, which is prepared by the above-mentioned preparation method of a photothermal super-hydrophobic anti-icing and deicing composite material based on a template collaborative ablation method.
[0029] The present invention discloses a photothermal super-hydrophobic anti-icing and deicing composite material based on a template collaborative ablation method. Based on the micro-nano structure of the material surface, this structure realizes the super-hydrophobic Cassie-Baxter model of the surface, the solid-liquid contact area fraction is reduced, the solid-gas contact area fraction is increased, and the shrinkage tendency of water droplets is increased, thereby increasing the apparent water contact angle, reducing the rolling angle, and reducing the adhesion of ice and other pollutants, thereby improving the passive anti-icing and anti-frost effect; under the blessing of sunlight, the photothermal filler can convert sunlight into thermal energy, increase the temperature of the material surface, and realize active deicing and defrost of the material. The preparation cost of the super-hydrophobic anti-icing and deicing material is low, the preparation efficiency is high, the preparation process is green and environmentally friendly, and it can be mass-produced in industry.
[0030] In order to achieve the third purpose of the above invention, the technical solution adopted by the present invention is as follows:
[0031] The present invention provides a photothermal super-hydrophobic anti-icing and deicing surface. The film surface is prepared by the above-mentioned method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on template collaborative ablation. By combining with light, it has excellent photothermal conversion performance, which is a good guarantee for subsequent photothermal anti-icing, anti-frost and deicing.
[0032] The photothermal super-hydrophobic anti-icing and deicing surface of the present invention has excellent hydrophobicity, anti-icing and deicing performance, and has low preparation cost and high preparation efficiency, and can be mass-produced in industry.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The present invention is a method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on a template collaborative ablation method. Common dry sandpaper is selected as a template. Sandpaper is a common material used for grinding. Silicon carbide abrasive is bonded to latex with synthetic resin as a binder. It has the advantages of anti-blocking, anti-static, good softness, high wear resistance, etc., and there are a variety of finenesses to choose from. Different finenesses have different microscopic roughnesses. As a template, the size of the microstructure of the hydrophobic film can be regulated. Compared with the existing reported "dry lotus leaf" and other natural plant surface template replication preparation technology, due to the low wear resistance of the surface of plants such as dry lotus leaves, the micro-nano structure of the surface is easily damaged after replication; however, in the present invention, the high hardness silicon carbide abrasive in the sandpaper increases the wear resistance, so that the microstructure of multiple replications remains basically unchanged; and the anti-blocking performance of the sandpaper makes it easy to separate the film from the sandpaper template after casting and curing into a film, which is more suitable for industrial large-scale production.
[0035] (2) The present invention is a method for preparing a photothermal super-hydrophobic anti-icing and de-icing composite material based on a template-coordinated ablation method, wherein photothermal nanoparticles are used as fillers and uniformly dispersed in a high molecular polymer, and then sandpaper is used as a template to form a film with a micro-pit structure by a casting and curing film-forming method, and then by flame ablation treatment, nano-folds or synapse-like nanoparticles are formed on the micro-pit structure of the film, thereby forming a super-hydrophobic surface with a micro-nano structure. The electrochemical deposition and laser ablation methods reported to construct nanostructures on microstructures have the advantage of being able to precisely control and obtain regular super-hydrophobic arrays, but are expensive, have a long processing time, and have high etching costs, making it difficult to achieve large-scale production; in comparison, flame ablation treatment to construct nano-folds or nanoparticles has low preparation costs and high preparation efficiency, and can achieve large-scale production in industry.
[0036] (3) The photothermal super-hydrophobic anti-icing and deicing composite material based on the template collaborative ablation method of the present invention uses photothermal nanoparticles as fillers. The nanoparticles have surface plasma resonance characteristics. When light is irradiated on the nanoparticles, surface plasma resonance is stimulated, causing the surface charge of the nanoparticles to oscillate continuously, thereby enhancing the absorption of light. The photothermal filler converts sunlight into thermal energy, increases the temperature of the material surface, and is a good guarantee for photothermal active anti-icing and anti-frost and active deicing. The photothermal super-hydrophobic anti-icing and deicing composite material based on the template collaborative ablation method of the present invention realizes the super-hydrophobic Cassie-Baxter model of the surface based on the micro-nano structure of the material surface. This micro-nano structure is a typical light trap structure. The absorbed light will undergo multiple internal reflections in the micro-pits, realizing a "light capture effect" without dead angles for sunlight, enhancing the photothermal conversion efficiency, and is conducive to improving the active deicing and defrost performance of the composite material.
[0037] Although super-hydrophobic surfaces have excellent passive anti-icing performance, most super-hydrophobic surface structures are easily damaged by external forces, thus affecting the anti-icing ability. Therefore, ice and frost on super-hydrophobic surfaces cannot be intervened by traditional mechanical deicing methods. The present invention combines active deicing by photothermal effect with super-hydrophobic surfaces to achieve the purpose of effective deicing and passive anti-icing at the same time, thereby eliminating the need to intervene by traditional mechanical deicing methods and avoiding external forces from destroying the super-hydrophobic surface structure.
[0038] (4) The template used in the present invention and the formation of the photothermal super-hydrophobic surface micro-nano structure make the entire preparation process of the super-hydrophobic anti-icing and de-icing material simple, with low preparation cost, short preparation time, and high preparation efficiency, which is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 It is a schematic diagram of the preparation process of a photothermal super-hydrophobic anti-icing and deicing composite material based on template collaborative ablation method according to Example 1 of the present invention.
[0041] Figure 2 : The SEM images of the sample without flame treatment and the sample after flame treatment. In the figure, group a is the SEM image of the sample N-PDMS without flame treatment (sandpaper of different meshes is used as template) and the smooth PDMS film of comparative example 2; group b is the SEM image of the sample F-PDMS after flame treatment (sandpaper of different meshes is used as template).
[0042] Figure 3 The following is the test result of water contact angle and sliding angle of the sample N-PDMS (sandpaper with different meshes as template) without flame treatment and the sample F-PDMS (sandpaper with different meshes as template) after flame treatment. In the figure, N-PDMS represents the sample without flame ablation treatment, F-PDMS represents the sample after flame ablation treatment, and WSA represents the sliding angle.
[0043] Figure 4 The SEM images of the film surface of F-PDMS (240#) and F-PDMS (400#) samples before and after 20 cycles of tape stripping are shown in Figure 1. In the figure, a represents the sample before the tape stripping test, and b represents the sample after the tape stripping test.
[0044] Figure 5 This is a liquid column bounce diagram of the super-hydrophobic surface of the material obtained in Example 1.
[0045] Figure 6 This is a comparison chart of the self-cleaning effects of sample 0.8C@PDMS (240#) without flame treatment after adding carbon black photothermal nanofiller and sample F-0.8C@PDMS (240#) after flame treatment on sand, soil, putty powder and carbon powder.
[0046] Figure 7 The temperature-time curve and infrared heat flow diagram of the photothermal performance of the film surface prepared by adding different carbon black nanoparticle contents. In the figure, a is the temperature-time curve diagram, and b is the infrared heat flow diagram.
[0047] Figure 8It is a comparison of the surface temperature curves of the samples F-0.8C@PDMS (240#) with added carbon black and F-PDMS (240#) without added carbon black, as well as the surface frost conditions at different stages.
[0048] Fig. 9 This is a diagram of the anti-icing test of the photothermal super-hydrophobic anti-icing and deicing composite material prepared in Example 1 based on the template collaborative ablation method when water droplets hit the surface at different temperatures.
[0049] Fig.10 This is a comparison diagram of the freezing process and completion time of water droplets on the surfaces of the unflame-treated samples PDMS (240#), 0.8C@PDMS (240#) and the flame-treated samples F-PDMS (240#), F-0.8C@PDMS (240#).
[0050] Fig.11 It is a comparison chart of the photothermal deicing process of the comparison samples PDMS (240#), 0.8C@PDMS (240#), F-PDMS (240#), and F-0.8C@PDMS (240#) and the time it takes for the ice on the surface to completely melt. DETAILED DESCRIPTION
[0051] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0052] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. In the present invention, the singular forms "a", "said" and "the" used in the embodiments and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0053] Sample naming scheme in the present invention
[0054]
[0055] In an embodiment of the present invention, a photothermal super-hydrophobic anti-icing and deicing composite material based on a template coordinated ablation method and a preparation method thereof include the following steps:
[0056] S1. preparing film-forming slurry: adding high molecular polymer and photothermal nanoparticles into an organic solvent, mixing them evenly, and preparing film-forming slurry;
[0057] S2, reverse molding: using sandpaper as a template, pouring the film-forming slurry prepared in step S1 on the surface of the sandpaper;
[0058] S3, curing and demoulding: heating and curing the film-forming slurry poured on the sandpaper surface in step S2, and then removing the sandpaper template to obtain a film with a micro-pit structure on the surface;
[0059] S4, flame ablation treatment: using flame to ablate the surface of the film obtained in step S3, so as to obtain the photothermal super-hydrophobic anti-icing and deicing composite material based on template coordinated ablation method.
[0060] A template-coordinated ablation method photothermal super-hydrophobic anti-icing and deicing composite material and its preparation method in the embodiment, using photothermal nanoparticles as fillers, uniformly dispersed in a high molecular polymer, using sandpaper as a template, forming a film with a micro-pit structure by a casting and curing film-forming method, and then by flame ablation treatment, nano-wrinkles or synapse-like nanoparticles are formed on the micro-pit structure of the film, thereby forming a super-hydrophobic surface with a micro-nano structure, and the prepared template-coordinated ablation method-based photothermal super-hydrophobic anti-icing and deicing composite material has excellent photothermal and hydrophobic properties. The present invention is simple in the entire preparation process of the super-hydrophobic anti-icing and deicing material, from the selection of the template to the formation of the micro-nano structure of the photothermal super-hydrophobic surface, with low preparation cost, short preparation time, and high preparation efficiency, and can be suitable for large-scale production.
[0061] In some embodiments, in step S1, the high molecular polymer is polydimethylsiloxane; polydimethylsiloxane is a high molecular polymer with low surface energy, and its film-forming material has good hydrophobic properties.
[0062] The photothermal nanoparticles are one of carbon black nanoparticles, ferroferric oxide nanoparticles or titanium dioxide nanoparticles; wherein the photothermal nanoparticles have excellent photothermal conversion performance. And / or
[0063] The organic solvent is one of n-hexane, ethyl acetate or tetrahydrofuran, wherein n-hexane, ethyl acetate or tetrahydrofuran are all easy to dissolve polymer compounds and are easy to volatilize during heating and curing.
[0064] In some embodiments, in step S1, the mass ratio of the high molecular weight polymer, the organic solvent and the photothermal nanoparticles is 1: (1.5-3): (0.002-0.01); and / or
[0065] The particle size of the photothermal nanoparticles is 20nm to 40nm; wherein the particle size of the photothermal nanoparticles can make the formed material have better hydrophobic properties. And / or
[0066] The uniform mixing is carried out by using a high-speed homogenizing and degassing machine. The speed of the high-speed homogenizing machine is 3000 rap to 4000 rap, and the homogenizing time is 3 min to 5 min. The degassing allows the film-forming slurry to better fit the sandpaper template, and the cured film can replicate the morphology of the sandpaper template, which can make the film more hydrophobic.
[0067] In some embodiments, in step S1, the film-forming slurry after being mixed evenly is further placed in a vacuum tank for vacuum degassing. Through further vacuum degassing, the film-forming slurry and the sandpaper template are better fitted, and the cured film can more highly and completely replicate the morphology of the sandpaper template, so that the obtained film can have excellent hydrophobic properties.
[0068] In some embodiments, in step S2, the mesh number of the sandpaper is 100-800 mesh. Preferably, the mesh number of the sandpaper is 240-400 mesh.
[0069] In some embodiments, in step S2, the sandpaper is fixed in a container, and then the film-forming slurry prepared in step S1 is poured on the surface of the sandpaper. The sandpaper is fixed in a container to facilitate the subsequent heating, curing and molding process.
[0070] In some embodiments, in step S3, the temperature of the heating and curing is 60° C. to 80° C., and the time of the heating and curing is 2 h to 4 h. The heating and curing is performed in an oven.
[0071] In some embodiments, in step S4, the flame is a flame of butane combustion; and / or
[0072] The temperature of the flame is 500° C. to 700° C., and the time of the fire roasting treatment is 5s to 25s.
[0073] In an embodiment of the present invention, a photothermal super-hydrophobic anti-icing and deicing composite material based on template collaborative ablation method is prepared by the above-mentioned preparation method of a photothermal super-hydrophobic anti-icing and deicing composite material based on template collaborative ablation method.
[0074] In the embodiment, a photothermal super-hydrophobic anti-icing and deicing composite material based on template collaborative ablation method has a hydrophobic surface formed by an environmentally friendly and efficient photothermal conversion super-hydrophobic anti-icing and deicing material. Under the blessing of sunlight, the photothermal temperature of the material can be increased, and the requirements of passive anti-icing and anti-frost and active deicing and defrosting can be met at the same time. The preparation cost of the super-hydrophobic anti-icing and deicing material is low, the preparation efficiency is high, it can be mass-produced in industry, and it has excellent hydrophobic properties.
[0075] In an embodiment of the present invention, a photothermal super-hydrophobic anti-icing and deicing surface is provided, and the film surface is prepared by the above-mentioned method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on template collaborative ablation method.
[0076] A photothermal super-hydrophobic anti-icing and deicing surface in the embodiment has excellent hydrophobic properties, low preparation cost, high preparation efficiency, and can be mass-produced in industry.
[0077] The following describes the invention in conjunction with specific embodiments.
[0078] Example 1
[0079] A method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on a template coordinated ablation method, such as Figure 1 As shown, the following steps are included:
[0080] S1. Prepare film-forming slurry: add polydimethylsiloxane and carbon black nanoparticles to n-hexane, and mix them evenly using a high-speed homogenizer and degasser to obtain film-forming slurry; the film-forming slurry after mixing evenly is further placed in a vacuum tank for vacuum degassing; in this embodiment, the mass ratio of polydimethylsiloxane, n-hexane and carbon black nanoparticles is 1:2:0.008; in this embodiment, the particle size of the carbon black nanoparticles is 30 nm;
[0081] S2, reverse molding: using 240-mesh sandpaper as a template, fixing the sandpaper in a container, and pouring the film-forming slurry prepared in step S1 on the surface of the sandpaper;
[0082] S3, curing and demoulding: the film-forming slurry poured on the sandpaper surface in step S2 is heated to 70° C. for curing for 3 hours, and then the sandpaper template is removed to obtain a film with a micro-pit structure on the surface;
[0083] S4, flame ablation treatment: flame ablation is performed on the surface of the film obtained in step S3 using a flame of butane combustion, so as to obtain the template-based photothermal nanofiller super-hydrophobic anti-icing and deicing material. In this embodiment, the flame temperature is 500° C. and the ablation treatment time is 20 seconds.
[0084] Example 2
[0085] A method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on a template coordinated ablation method comprises the following steps:
[0086] S1. Prepare film-forming slurry: add polydimethylsiloxane and carbon black nanoparticles to n-hexane, and mix them evenly with a high-speed homogenizer to obtain film-forming slurry; the film-forming slurry after mixing evenly is further placed in a vacuum tank for vacuum degassing; in this embodiment, the mass ratio of polydimethylsiloxane, n-hexane and carbon black nanoparticles is 1:1.5:0.002; in this embodiment, the particle size of the carbon black nanoparticles is 20 nm;
[0087] S2, reverse molding: using 400-mesh sandpaper as a template, fixing the sandpaper in a container, and pouring the film-forming slurry prepared in step S1 on the surface of the sandpaper;
[0088] S3, curing and demoulding: the film-forming slurry poured on the sandpaper surface in step S2 is heated to 60° C. for curing for 4 hours, and then the sandpaper template is removed to obtain a film with a micro-pit structure on the surface;
[0089] S4, flame ablation treatment: flame ablation is performed on the surface of the film obtained in step S3 using a flame of burning butane, so as to obtain the template-based photothermal nanofiller super-hydrophobic anti-icing and deicing material. In this embodiment, the flame temperature is 700° C. and the ablation treatment time is 5 seconds.
[0090] Example 3
[0091] A method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on a template coordinated ablation method comprises the following steps:
[0092] S1. Prepare film-forming slurry: add polydimethylsiloxane and carbon black nanoparticles to n-hexane, and mix them evenly with a high-speed homogenizer to obtain film-forming slurry; the film-forming slurry after mixing evenly is further placed in a vacuum tank for vacuum degassing; in this embodiment, the mass ratio of polydimethylsiloxane, n-hexane and carbon black nanoparticles is 1:3:0.01; in this embodiment, the particle size of the carbon black nanoparticles is 40 nm;
[0093] S2, reverse molding: using 100-mesh sandpaper as a template, fixing the sandpaper in a container, and pouring the film-forming slurry prepared in step S1 on the surface of the sandpaper;
[0094] S3, curing and demoulding: the film-forming slurry poured on the sandpaper surface in step S2 is heated to 80° C. for curing for 2 hours, and then the sandpaper template is removed to obtain a film with a micro-pit structure on the surface;
[0095] S4, flame ablation treatment: flame ablation is performed on the surface of the film obtained in step S3 using a flame of burning butane, so as to obtain the template-based photothermal nanofiller super-hydrophobic anti-icing and deicing material. In this embodiment, the flame temperature is 600° C. and the ablation treatment time is 25 seconds.
[0096] Example 4
[0097] A method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on a template coordinated ablation method comprises the following steps:
[0098] S1. Prepare film-forming slurry: add polydimethylsiloxane and carbon black nanoparticles to n-hexane, and mix them evenly with a high-speed homogenizer to obtain film-forming slurry; the film-forming slurry after mixing evenly is further placed in a vacuum tank for vacuum degassing; in this embodiment, the mass ratio of polydimethylsiloxane, n-hexane and carbon black nanoparticles is 1:2.5:0.005; in this embodiment, the particle size of the carbon black nanoparticles is 25 nm;
[0099] S2, reverse molding: using 800-mesh sandpaper as a template, fixing the sandpaper in a container, and pouring the film-forming slurry prepared in step S1 on the surface of the sandpaper;
[0100] S3, curing and demoulding: the film-forming slurry poured on the sandpaper surface in step S2 is heated to 65° C. for curing for 3.5 hours, and then the sandpaper template is removed to obtain a film with a micro-pit structure on the surface;
[0101] S4, flame ablation treatment: flame ablation treatment is performed on the surface of the film obtained in step S3 using a flame of butane combustion, so as to obtain the template-based photothermal nanofiller super-hydrophobic anti-icing and deicing material. In this embodiment, the flame temperature is 600° C. and the ablation treatment time is 8 seconds.
[0102] Example 5
[0103] A method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on a template coordinated ablation method comprises the following steps:
[0104] S1. Prepare film-forming slurry: add polydimethylsiloxane and carbon black nanoparticles to n-hexane, and mix them evenly with a high-speed homogenizer to obtain film-forming slurry; the film-forming slurry after mixing evenly is further placed in a vacuum tank for vacuum degassing; in this embodiment, the mass ratio of polydimethylsiloxane, n-hexane and carbon black nanoparticles is 1:1.8:0.006; in this embodiment, the particle size of the carbon black nanoparticles is 35 nm;
[0105] S2, reverse molding: using 180-mesh sandpaper as a template, fixing the sandpaper in a container, and pouring the film-forming slurry prepared in step S1 on the surface of the sandpaper;
[0106] S3, curing and demoulding: the film-forming slurry poured on the sandpaper surface in step S2 is heated to 75° C. for curing for 2.5 hours, and then the sandpaper template is removed to obtain a film with a micro-pit structure on the surface;
[0107] S4, flame ablation treatment: flame ablation treatment is performed on the surface of the film obtained in step S3 using a flame of butane combustion, so as to obtain the template-based photothermal nanofiller super-hydrophobic anti-icing and deicing material. In this embodiment, the flame temperature is 500° C. and the ablation treatment time is 10 seconds.
[0108] Example 6
[0109] A method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on a template collaborative ablation method. The difference between this embodiment and Example 1 is that the photothermal nanoparticles of this embodiment are ferroferric oxide nanoparticles, the organic solvent of this embodiment is ethyl acetate, and the remaining components and preparation method are the same as those of Example 1.
[0110] Example 7
[0111] A method for preparing a photothermal superhydrophobic anti-icing and deicing composite material based on a template collaborative ablation method. The difference between this embodiment and Example 1 is that the photothermal nanoparticles of this embodiment are titanium dioxide nanoparticles, the organic solvent of this embodiment is tetrahydrofuran, and the remaining components and preparation method are the same as those of Example 1.
[0112] Example 8
[0113] A photothermal super-hydrophobic surface is a film surface prepared by any one of the preparation methods of photothermal super-hydrophobic anti-icing and deicing composite materials based on template collaborative ablation method according to Examples 1 to 7.
[0114] Comparative Example 1
[0115] A method for preparing a thin film material. The difference between this comparative example and Example 1 is that the flame ablation treatment in step S4 is not performed in this comparative example, and a thin film with a micro-pit structure on the surface is obtained after steps S1 to S3.
[0116] Comparative Example 2
[0117] A method for preparing a thin film material. The difference between this comparative example and Example 1 is that this comparative example does not use a template and does not perform the flame ablation treatment of step S4. The film-forming slurry obtained in step S1 of Implementation 1 is directly cured and formed to obtain a smooth PDMS thin film sample.
[0118] Surface morphology and performance testing
[0119] 1. Effect of preparation process conditions on PDMS-based superhydrophobic surface morphology and wetting properties
[0120] Using the preparation steps S1 to S3 in Example 1, the mesh sizes of sandpaper were 100 mesh, 180 mesh, 240 mesh, 400 mesh and 800 mesh, respectively, to prepare five samples of thin films with micro-pit structures on the surface, marked as sample N-PDMS (sandpaper of different mesh sizes was used as template).
[0121] The smooth PDMS film sample prepared in Comparative Example 2 is marked as N-PDMS.
[0122] The morphology of the above six thin film samples was characterized by scanning electron microscopy (SEM). The characterization results can be found in Figure 2 (a) shown.
[0123] Depend on Figure 2 (a) It can be seen that the surface of the PDMS film constructed using sandpaper of different meshes as the template, during the casting and curing process, the PDMS film formed by the film-forming slurry well replicates the microstructure of the sandpaper template. In addition, the PDMS film constructed using sandpaper of different meshes as the template has micro-pits of different sizes. However, the smooth PDMS film without sandpaper as the template, such as Figure 2 As shown in (a), the N-PDMS surface is smooth and has no micro-pit structure.
[0124] Preparation of flame-treated samples: The N-PDMS samples (sandpapers of different mesh sizes as templates) prepared above were all sampled and flame-treated according to the method of Example 1. The obtained samples were uniformly labeled as F-PDMS (sandpapers of different mesh sizes as templates).
[0125] Scanning electron microscopy (SEM) was used to examine F-PDMS (sandpaper with different mesh sizes was used as template) samples, and the effect of flame ablation treatment on the surface morphology of the film was compared and analyzed. Figure 2 As shown in (b), after flame treatment, dense nanoparticles were generated on the surface of each F-PDMS sample (sandpaper of different mesh sizes was used as template). The formation of these nanostructures may come from the following two aspects: (1) the butane flame is not fully burned, which may deposit a small number of carbon nanoparticles on the concave and convex parts of the film surface; (2) during the short-term ablation of the flame treatment, the film surface is subjected to thermal stress due to heating, which in turn causes slight deformation of the surface layer, resulting in the formation of nanoscale wrinkles and synapses on the film surface.
[0126] Water contact angle and sliding angle (WSA) detection: The water contact angle and sliding angle of the N-PDMS sample (sandpaper of different meshes as template) and the flame ablation sample F-PDMS (sandpaper of different meshes as template) prepared above were respectively tested. The test results are shown in Figure 2. Figure 3 shown.
[0127] Depend on Figure 3From the test results, it can be seen that the water contact angle on the surface of the N-PDMS sample (sandpaper of different mesh sizes used as templates) that has not been flame ablated is about 120°. Compared with the surface of the smooth PDMS film sample ∝, the increase in the water contact angle is almost negligible, and no superhydrophobic properties are exhibited. On the contrary, the water contact angle of the F-PDMS sample (sandpaper of different meshes was used as template) after a short flame ablation treatment (20 seconds) was significantly improved. Except for the smooth PDMS film sample ∝ surface, the water contact angles of the F-PDMS surfaces corresponding to the sandpaper templates of different meshes 100#, 180#, 240#, 400# and 800# were all around 150°, especially the water contact angle of the F-PDMS surface corresponding to the sandpaper templates of 240#, 400# and 800# were close to 160°, and the sliding angles (WSA) were all below 5°, indicating that the water wetting performance of the surface of the composite material sample with micro-nano structure prepared by the template coordinated ablation method was significantly reduced, achieving excellent superhydrophobic performance.
[0128] 2. Durability of PDMS-based superhydrophobic surface
[0129] The surface of F-PDMS (240#) and F-PDMS (400#) was measured and compared after 20 tape stripping tests. The water contact angles of the super-hydrophobic surfaces of F-PDMS (240#) and F-PDMS (400#) decreased from 159° and 155° to 156° and 152° respectively after 20 cycles of tape stripping experiments. The decrease was small, and the water contact angle was still above 150°, which showed super-hydrophobic properties. In order to analyze the reasons, SEM images of the samples before and after the tape stripping test were taken, as shown in the figure. Figure 4 As shown in the figure, the size and distribution of micro-pits on the PDMS surface prepared by using 240# and 400# grit sandpaper as templates may play an effective protective role for the nanostructure during the tape stripping process. Although the nanostructure of the protruding parts between some micro-pits is destroyed, the dense distribution and appropriate size of the micro-pits retain most of the nanostructure, thus showing good super-hydrophobic durability, which effectively solves the technical problem that the super-hydrophobic surface of conventional micro-nanostructure is easily damaged and not durable.
[0130] 3. Morphology and wetting properties of photothermal superhydrophobic surfaces
[0131] The photothermal super-hydrophobic anti-icing and deicing material prepared in Example 1 was used to demonstrate its wettability. Figure 5 As shown, the droplet presents a complete spherical shape on its surface; similarly, when water impacts the sample surface in a flowing state, the water column still maintains the shape of a water column and bounces off. This phenomenon well illustrates the excellent superhydrophobic and water-repellent properties of the surface of the photothermal superhydrophobic anti-icing and deicing composite material prepared by the template coordinated ablation method of the present invention.
[0132] 4. Self-cleaning performance of photothermal superhydrophobic surface
[0133] The samples prepared in Example 1 and Comparative Example 1 are marked as F-0.8C@PDMS (240#) and 0.8C@PDMS (240#), respectively, and the self-cleaning effects of sand, soil, putty powder and carbon powder are compared, as shown in Figure 6. Figure 6 It can be seen that the super-hydrophobic sample F-0.8C@PDMS (240#) has self-cleaning properties for common pollutants such as sand, dirt, putty powder and carbon powder. These pollutants basically do not adhere to the surface, keeping the surface dry. However, the surface of the sample 0.8C@PDMS (240#) without ablation treatment has some pollutants such as sand, dirt, putty powder and carbon powder adhered to the surface, indicating that ablation treatment is crucial to improving the super-hydrophobic and anti-fouling properties of the surface.
[0134] 5. Photothermal response of photothermal super-hydrophobic surface
[0135] The preparation method of Example 1 was adopted, and carbon black nanoparticles of different mass fractions were added to prepare film samples with carbon black contents of 0wt%, 0.2wt%, 0.5wt%, 0.8wt% and 1wt%, respectively. The mass ratios of polydimethylsiloxane to carbon black nanoparticles in the samples with the above percentages were 0, 1:0.002, 1:0.005, 1:0.008 and 1:0.01, respectively.
[0136] Among them, the temperature-time curve of the photothermal performance of the film surface prepared with different carbon black nanoparticle contents is as follows: Figure 7 (a) shows the photothermal characteristics of the film surface prepared with different carbon black nanoparticle contents. The infrared heat flow diagram is shown below. like Figure 7 (b) as shown.
[0137] At an optical power density of 100 mW / cm 2 Simulate sunlight irradiation and record the temperature-time curve corresponding to each group of samples, such as Figure 7 As shown in (a). Among them, the surface of the PDMS-based film with a carbon black nanoparticle content of 0wt% only rises to 59.1°C within 180s under illumination, relying on the heat gain of sunlight. The surfaces of other PDMS-based films with added carbon black nanoparticles all clearly show the phenomenon of photothermal warming, and as the carbon black content increases from 0.2wt% to 0.8wt%, the maximum temperature that can be reached also increases from 69°C to 83°C. It can be seen that the surface of the photothermal super-hydrophobic anti-icing and deicing composite material based on the template collaborative ablation method prepared by the present invention has good photothermal conversion performance, which is a guarantee for subsequent photothermal anti-icing, anti-frost and deicing work.
[0138] VI. Photothermal anti-frost performance of photothermal super-hydrophobic surface
[0139] The surface of the photothermal super-hydrophobic anti-icing and de-icing composite material based on the template collaborative ablation method prepared by the present invention shows good water repellency and greatly reduces the possibility of ice formation. However, when it is in a low temperature and high humidity environment for a long time, water vapor condenses on the super-hydrophobic surface to form ice crystals. The ice crystals will cover the surface microstructure, causing the surface to become irregular and uneven, thereby destroying the original super-hydrophobic properties. In addition, the formation of ice crystals also increases the surface energy of the surface, which enhances the surface's attraction to water, further reducing the water repellency. In a low temperature and high humidity environment, anti-frost or defrosting by combining photothermal effect with super-hydrophobicity has significant advancement and feasibility. The above-mentioned marked sample F-0.8C@PDMS (240#) and the control group sample F-PDMS (240#) without the addition of photothermal carbon black were placed on a semiconductor refrigeration sheet at -15°C, with an ambient humidity of 80%. Under the same light power density irradiation, the changes in the surface temperature of the two groups over time were recorded as follows. Figure 8 (a) shows the process of frost formation and photothermal defrosting on the surfaces of the two groups of samples. Figure 8 (b) As shown. The experimental results show that the control sample F-PDMS (240#) without the addition of photothermal nanocarbon black, under the irradiation of light power density, even if the surface temperature is increased, but in the detection time range, the surface temperature is always below 0°C, so the frost on the surface is not completely removed; on the contrary, the sample F-0.8C@PDMS (240#) has excellent photothermal efficiency and can quickly heat up under light irradiation. This rapid heat generation can quickly melt the frost on the surface and thaw it quickly. This autonomous anti- / defrosting performance makes the superhydrophobic surface without additional energy consumption during the anti-frost process, saving energy and cost. At the same time, heat is continuously generated in the presence of light, so it can continue to maintain a thawed state. This makes it have a more lasting effect in continuous anti-frost applications without frequent intervention or energy replenishment.
[0140] VII. Anti-icing performance of photothermal super-hydrophobic surface
[0141] ① Low temperature water droplet impact experiment
[0142] The template-coordinated ablation photothermal super-hydrophobic anti-icing and deicing composite material (labeled as F-0.8C@PDMS (240#)) prepared in Example 1 was subjected to a low-temperature water droplet impact experiment. Fig. 9As shown, the bouncing of droplets on the surface of F-0.8C@PDMS (240#) was recorded at 25°C, -5°C and -10°C. The results show that the droplet bouncing heights are 1.5mm, 1.2mm and 1mm respectively, and the droplets can still maintain good bouncing ability at a temperature of -10°C, indicating that the surface of F-0.8C@PDMS (240#) can still maintain good water repellency in a low temperature and high humidity environment within -10°C (humidity is 80%). In a low temperature environment of -10°C, the droplets basically do not adhere to the surface, thereby greatly reducing the risk of freezing. The surface properties of the photothermal superhydrophobic anti-icing and deicing composite material based on template collaborative ablation method prepared by the present invention are suitable for ordinary low temperature environments.
[0143] ②Icing delay test
[0144] The above-labeled samples PDMS (240#), 0.8C@PDMS (240#), F-PDMS (240#), and F-0.8C@PDMS (240#) were subjected to icing delay tests respectively.
[0145] A water droplet with a volume of 5 μL was placed on the test surface of each sample, and the semiconductor refrigerator was started for cooling. During the cooling process, when the surface temperature reached 0°C, a high-speed CCD camera was used to record the freezing process (freezing start delay time). The cooling continued until the surface temperature stabilized at -20±0.5°C, and a sharp tip appeared on the top of the droplet, indicating that the ice formation process had ended, and the corresponding time was recorded. The freezing time (such as PDMS (240#), 0.8C@PDMS (240#), F-PDMS (240#) and F-0.8C@PDMS (240#) on four different surfaces was tested and recorded. Fig.10 (b)) and the freezing process (as shown in Fig.10 (as shown in (a)).
[0146] Depend on Fig.10It can be seen that the tip of the droplet was observed on the surface of the sample PDMS (240#) in 83s. The freezing time of the sample 0.8C@PDMS (240#) with added carbon black nanoparticles was 75s, and the freezing time was shortened to a certain extent; on the contrary, the freezing time of the samples F-PDMS (240#) and F-0.8C@PDMS (240#) with superhydrophobic properties was extended to 195s and 200s respectively, and the freezing time was nearly 2.5 times that of the sample PDMS (240#) without superhydrophobic properties. The test results are consistent with the previous superhydrophobic performance law, that is, the surface with good superhydrophobic performance prepared by the present invention has a significant performance of delaying freezing, which intuitively shows that the freezing time is closely related to the superhydrophobic performance. The main reason for superhydrophobic anti-icing is the micro-nano structure and low surface energy characteristics of the surface. On the one hand, the micro-nano structure makes it impossible for the droplet to fully unfold on the surface, reducing the contact area with the solid surface, thereby reducing the possibility of freezing. On the other hand, the low surface energy reduces the interaction force between the droplets and the surface, making it difficult to form sufficient solidification nuclei, thus delaying the occurrence of freezing.
[0147] 8. Photothermal deicing performance of photothermal super-hydrophobic surface
[0148] The surface of the photothermal super-hydrophobic anti-icing and deicing composite material prepared by the template collaborative ablation method of the present invention has good photothermal anti-icing / frost performance. Since the micro-nano structures of most super-hydrophobic surfaces in the prior art cannot withstand the structural damage caused by mechanical deicing, the use of sustainable energy solar energy for photothermal deicing is highly efficient and environmentally friendly. The present invention adopts an experiment similar to the above-mentioned ice delay. After the surface droplets are completely frozen, the surface temperature continues to be maintained at -20°C, and 100mW / cm 2 The surface was irradiated with a xenon lamp (one sun intensity), and the melting of ice and melting time during the photothermal process were photographed and recorded. The results are as follows: Fig.11 As shown in Figure 1. Among them, the photothermal deicing process diagram is as follows: Fig.11 (a) shows the time it takes for the surface ice drop to completely melt. Fig.11 (b) as shown.
[0149] Depend on Fig.11It can be seen that although the sample F-PDMS (240#) with a superhydrophobic surface has a good ice delay time, it lacks the ability to convert light to heat. During the 150s irradiation time, only the tip of the ice droplet melts slightly. In contrast, the sample PDMS (240#) lacks superhydrophobic properties and photothermal conversion capabilities, and the ice droplet not only does not melt slightly, but is covered with a large amount of frost on the surface. For the samples F-0.8C@PDMS and 0.8C@PDMS with photothermal conversion capabilities, the melting time of the ice droplet is shortened, and the melting of the ice droplet is completed within the irradiation time of 135s and 143s, respectively. This shows that the sample F-0.8C@PDMS (240#) prepared by the present invention not only has good performance in superhydrophobic anti-icing and photothermal anti- / defrosting, but also has outstanding performance in photothermal deicing.
[0150] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A photothermal super-hydrophobic anti-icing and deicing composite material based on template collaborative ablation method and a preparation method thereof, characterized in that: The following steps are involved: S1. preparing film-forming slurry: adding high molecular polymer and photothermal nanoparticles into an organic solvent, mixing them evenly, and preparing film-forming slurry; S2, reverse molding: using sandpaper as a template, pouring the film-forming slurry prepared in step S1 on the surface of the sandpaper; S3, curing and demoulding: heating and curing the film-forming slurry poured on the sandpaper surface in step S2, and then removing the sandpaper template to obtain a film with a micro-pit structure on the surface; S4, flame ablation treatment: using flame to ablate the surface of the film obtained in step S3, so as to obtain the photothermal super-hydrophobic anti-icing and deicing composite material based on template coordinated ablation method.
2. The method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on template coordinated ablation method according to claim 1, characterized in that: In the step S1, the high molecular polymer is polydimethylsiloxane; and / or The photothermal nanoparticles are one of carbon black nanoparticles, ferroferric oxide nanoparticles or titanium dioxide nanoparticles; and / or The organic solvent is one of n-hexane, ethyl acetate or tetrahydrofuran.
3. The method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on template coordinated ablation method according to claim 1, characterized in that: In the step S1, the mass ratio of the high molecular weight polymer, the organic solvent and the photothermal nanoparticles is 1:(1.5-3):(0.002-0.01); and / or The particle size of the photothermal nanoparticles is 20nm to 40nm; and / or The uniform mixing is carried out by using a high-speed homogenizing and degassing machine.
4. The method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on template coordinated ablation method according to claim 1, characterized in that: In the step S1, the uniformly mixed film-forming slurry is further placed in a vacuum tank for vacuum degassing.
5. The method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on template coordinated ablation method according to claim 1, characterized in that: In the step S2, the mesh number of the sandpaper is 100-800 mesh.
6. The method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on template coordinated ablation method according to claim 1, characterized in that: In the step S2, the sandpaper is fixed in a container, and then the film-forming slurry obtained in the step S1 is poured on the surface of the sandpaper.
7. The method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on template coordinated ablation method according to claim 1, characterized in that: In the step S3, the temperature of the heating and curing is 60° C. to 80° C., and the time of the heating and curing is 2 h to 4 h.
8. The method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on template coordinated ablation method according to claim 1, characterized in that: In step S4, the flame is a flame of butane combustion; and / or The temperature of the flame is 500° C. to 700° C., and the time of the ablation treatment is 5s to 25s.
9. A photothermal super-hydrophobic anti-icing and deicing composite material based on template collaborative ablation method, characterized in that: The photothermal super-hydrophobic anti-icing and deicing composite material is prepared by the preparation method based on template collaborative ablation method as described in any one of claims 1 to 8.
10. A photothermal super-hydrophobic anti-icing and de-icing surface, characterized in that: The film surface is prepared by the method for preparing a photothermal super-hydrophobic anti-icing and deicing composite material based on template collaborative ablation as described in any one of claims 1 to 8.
Citation Information
Patent Citations
All-parameter controllable preparation method for super-hydrophobic micro-nano composite structure
CN106185792A
PDMS superhydrophobic surface preparation method based on template technology
CN110746624A
Photoelectric-thermal superhydrophobic film, preparation method thereof and anti-icing and deicing application
CN111716776A
Method for preparing super-hydrophobic material by taking abrasive paper as template
CN112552687A
Super-hydrophobic photo-thermal deicing coating as well as preparation method and application thereof
CN116535715A
Cited By
Fluorine-free super-hydrophobic photo-thermal anti-icing coating, method and application thereof
CN121471816A